SMOKING AS A PREDICTOR OF IMMUNE CHECKPOINT INHIBITOR EFFICACY IN METASTATIC NON-SMALL CELL LUNG CANCER PATIENTS - Moskalenko, Yuliia; Bohdanov, Anton; Budko, Vitalii (Eastern Ukrainian Medical Journal, 2025)
Immunotherapy is currently the most promising treatment approach for metastatic non-small cell lung cancer (mNSCLC). Despite significant improvements clinical outcomes, prognostic criteria for responses to immune checkpoint inhibitors (ICIs) remain evasive. Smoking is one of the most common causes of lung cancer. However, several studies have confirmed the positive prognostic value of smoking in patients treated with ICI.The aim of the study was to evaluate the prognostic significance of smoking status in mNSCLC patients treated with ICIs and to compare clinical outcomes by type of medication therapy and smoking history.Materials and methods. This retrospective cohort study included 205 patients with mNSCLC treated at Sumy Regional Clinical Oncology Center (2016–2024). Among them, 105 patients received ICI therapy (atezolizumab or pembrolizumab), and 100 received platinum-based chemotherapy. Patients were stratified into never-smokers, light smokers (<28 pack-years), and heavy smokers (≥28 pack-years). Clinical outcomes – progression-free survival (PFS), overall survival (OS), and objective response rate (ORR) – were analyzed using Kaplan–Meier and Cox regression models.Results. In the immunotherapy group, heavy smokers exhibited significantly better PFS (15.3 vs. 8.5 and 8.1 months; p=0.0001), OS (23.3 vs. 12.6 and 9.7 months; p=0.0013), and ORR (75.6% vs. 41.9% and 23.8%) compared to light smokers and never-smokers. Conversely, in the chemotherapy group, non-smokers had superior outcomes. PD-L1 overexpression and heavy smoking were identified as independent predictors of improved survival in ICI-treated patients (p<0.05).Conclusion. Heavy smokers receiving ICI therapy experienced more prolonged survival and better objective response rates than light smokers and never-smokers. In contrast, smokers treated with chemotherapy or chemoradiotherapy had worse survival and objective response rates than never-smokers.